2016
DOI: 10.1039/c5cc10112c
|View full text |Cite
|
Sign up to set email alerts
|

Pure white light emission from organic molecules using solvent induced selective self-assembly

Abstract: Organic materials generating pure white light emission have attracted considerable attention in recent times due to their potential applications in lighting and display devices. We have used anthracene carboxylic acid (AnA) and anthracene carbaldehyde (AnC) to generate white light using solvent induced selective self-assembly (SISSA). Mechanistically, SISSA prevents a fast intersystem crossing of the AnC monomer and generates an emissive state from the self-assembled AnC. While AnA emits in the blue region, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…To evaluate the obtainedc olors, their CIE coordinates were calculated from the fluorescences pectra of solutionsc ontaining 6 and varying amountso fB (C 6 F 5 ) 3 (Figures 4a nd S31, Table S3). Under excitation at 365 nm and continuous addition of B(C 6 [14,15] In contrast, the present white-light emission is achieved by adding an onfluorescent Lewis acid to a5 -aminothiazole as as ingle-component fluorescent dye [7,26] with ab road emission band (400-700 nm).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…To evaluate the obtainedc olors, their CIE coordinates were calculated from the fluorescences pectra of solutionsc ontaining 6 and varying amountso fB (C 6 F 5 ) 3 (Figures 4a nd S31, Table S3). Under excitation at 365 nm and continuous addition of B(C 6 [14,15] In contrast, the present white-light emission is achieved by adding an onfluorescent Lewis acid to a5 -aminothiazole as as ingle-component fluorescent dye [7,26] with ab road emission band (400-700 nm).…”
mentioning
confidence: 92%
“…Interactions between fluorescent Lewis bases and non-fluorescento rganoboranes [12,13] are also expectedt od isplay multicolor emissions, and the combination of such emissions may provide access to white light. [14,15] We have previously reported that the fluorescencep roperties of 5-N-arylaminothiazole 1 (Scheme 1) can be controlled by the substituents, andt hat the presence of electron-donating groups on the nitrogen atom at the 5-position bathochromically shifts the emission. [16] 5-Aminothiazole 1 contains monocyclic homo-a nd heteroaromatic groups,w hereby their conformation is intricately correlatedt ob oth solventa nd temperature.…”
mentioning
confidence: 99%
“…are the different photophysical processes used to achieve panchromatic emission . In addition, the presence of external stimuli like pH and heat can also affect the photophysics of an organic emitter in the ground and the excited state, leading to tunable emission . Approaches involving the triplet state for the development of white light emitting organic phosphors, and thermally activated delayed fluorescence (TADF) emitters have become popular over last few years .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the tuning of energy transfer processes through a subtle balance between different luminophores is a prerequisite. Supramolecular self‐assembly approaches have been found to be effective for the generation of WLE materials . Considering an environmental disposal perspective, the fabrication of WLE materials using non‐hazardous substances and eco‐friendly solvents like water has drawn significant attention .…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular self-assembly approachesh ave been found to be effective for the generation of WLEm aterials. [28][29][30][31][32][33] Consideringa ne nvironmental disposal perspective,t he fabrication of WLE materials using non-hazardouss ubstances and eco-friendly solvents like water has drawnsignificant attention. [18,20,[34][35][36][37][38] Würthner and co-workersd emonstrated FRET between biscarbazole (energy donor) loadedi nto the hydrophobicc ore of perylene bisimidem icelles (energya cceptor) leading to white-light emission.…”
Section: Introductionmentioning
confidence: 99%